Pengembangan Sistem Manajemen Keuangan Rumah Sakit Prof. DR. J.A. Latumeten Ambon Yang Terintegrasi - Mustofa, Endri; Prasandi, Santika (ISAS, 2025)
Various internal and external challenges in hospital financial management, such as high operational costs, complex insurance cost management, and so on, require good financial governance or financial management. Increasing operational costs, demands for higher accountability from regulators and patients, and the need to make quick strategic decisions, encourage hospitals to have an efficient management system. The Integrated Hospital Financial Management System (SMKRST) is a technology-based information system designed to manage, track, and analyze all financial and operational transactions within the hospital environment in a comprehensive and integrated manner. Keywords: Hospital financial operational system, hospital financial management.